The social and cultural history of the provincial fair in England, 1750-1850 - Davidson, J (2018)
This thesis seeks new ways to explain and explore the social and cultural history of fairs in provincial England between 1750 and 1850. It approaches the history of fairs from within and is primarily concerned with the experiences and priorities of those who organised and attended these events. It argues that fairs remained much more important to a much wider range of people and activities than has previously been supposed. The first of four chapters of this thesis explores the role fairs played in the commercial networks and business practices of those trading goods, livestock, and entertainment there. The second considers links between fairs and the institutions of urban governance, uncovering the way in which fairs and their associated privileges and rituals both shaped and were used to communicate civic identities. The third examines the ways in which individuals understood the temporally and geographically liminal place of fairs in relation to the annual calendar, the lifecycle, and more permanent uses of urban space. Finally, the fourth chapter explores how the roles and meanings of fairs were presented and distorted in art, literature, and other cultural forms, and how the attitudes portrayed in these media in turn influenced the progression of these events. By reassessing fairs in light of more established historiographies of commerce and civic identity as well as bringing new approaches to the discussion of these events, this thesis seeks to disrupt the existing narrative of the history of fairs and sketch the outline of a new narrative that is richer and more variegated. In doing so it invites a renewed challenge to the boundaries that have been asserted between business and pleasure, polite and popular, and rural and urban in this period.